Pursuing Insights about Healthcare Utilization via Geocoded Search Queries - Yang, Shuang-Hong; White, Ryen W.; Horvitz, Eric (SIGIR'13, July 28-August 1, 2013, Dublin, Ireland, 2013)
Mobile devices provide people with a conduit to the rich information resources of the Web. With consent, the devices can also provide streams of information about search activity and location that can be used in population studies and real-time assistance. We analyzed geotagged mobile queries in a privacy-sensitive study of potential transitions from health information search to in-world healthcare utilization. We note differences in people’s health information seeking before, during, and after the appearance of evidence that a medical facility has been visited. We find that we can accurately estimate statistics about such potential user engagement with healthcare providers. The findings highlight the promise of using geocoded search for sensing and predicting activities in the world.